Easy Multiplication from Left to Right and Al Khwarizmi Method: Hypothesis Testing Against Median Values - Endro Tri Susdarwono (MEJ (Mathematics Education Journal), 2021)
This study aims to provide an overview of easy multiplication with the left to right method and also the right to left method (Al Khawarizmi Method). Furthermore, from easy multiplication with 2 methods, a test is carried out to determine the level of ease in its application to the two methods of multiplication. The method used in this research is experimental. While the approach in this research used is quantitative. The quantitative approach used includes testing the hypothesis on the median value. The conclusion of this study is that the median value of the posttest value of easy multiplication from left to right and easy multiplication from right to left is the same. Since the median is also the average value, it can also be concluded that the average number of easy multiplication posttest scores from left to right and easy multiplication posttest scores from right to left are the same. As an implication, the two easy multiplication techniques are able to produce the same level of convenience.